Effects of different basal media and complex additives interaction on in vitro seed germination and seedling growth of petai belalang (leucaena leucocephala) - Wong, Jackson Pak Seng (Universiti Malaysia Sarawak (UNIMAS), 2015)
Leucaena leucocephala or petai belalang has been identified as one of the best nitrogen fixing, standard sized fast growing leguminous tree that grows well in Malaysia. Their wood, which have a high density and energy value together with various biochemical compounds, make it an excellent biomass and feedstock to manufacture a variety of valuable products; caused it has a high market demand. However, conventional propagation method of L. leucocephala does not guarantee a high seed germination rate and the seedling growth as exhibition of natural seed dormancy and the seedling is susceptible to Phytophthora drechsleri and Fusarium semitectum. Thus, this research is performed to determine the interaction of different basal media and complex additives on in vitro seed germination and the seedling growth of L. leucocephala with the purpose to enhance the seed germination and the seedling growth of L. leucocephala. To address this, seeds were undergo sterilization followed by seed pre-treatment. The seeds were then cultured onto various basal media (half and full strength MS medium and Gamborg B5 medium) with or without the supplementation of complex additives (banana homogenate, potato homogenate and coconut water) with different concentrations. The results showed that Gamborg B5 media gave the highest seed germination whereas MS media showed the least seed germination efficiency. It was found that supplementation of complex additives had no effect on seed germination. However, media with complex additives showed the positive effect on seedling growth of L. leucocephala. 10% coconut water was found to give the most significant effect towards the seedling growth. By the end of this study, the L. leucocephala seedlings are able to be produced in vast amount to meet the high market demand.